Cartilage morphology assessed by high resolution micro-computed tomography in non OA knees. Issue 3 (March 2016) - Delecourt, C.; Relier, M.; Touraine, S.; Bouhadoun, H.; Engelke, K.; Laredo, J.D.; Chappard, C.
Summary: Objective: At the microscopic level, there is no established 3D method to measure cartilage volume and thickness. An easy, precise and accurate volume and thickness measurements of human cartilage has been developed from micro-computed tomography (micro-CT) images. Design: In the medial tibial plateau of twenty nine left cadaveric knees classified as normal, vertical cores (7 mm in diameter) were extracted in three locations: lateral (LAT), medial posterior (MP) and medial anterior (MA). The cores were imaged in mineral oil with micro-CT (voxel size 10.2 μm) and were measured cartilage volume (Cart.Vol, mm 3 ) and cartilage thickness (Cart.Th, mm) using a thickness plugin. Short term reproducibility and standard deviation (ST_RMSCV%, ST_RMSSD, mm) were determined. To assess accuracy, holes with diameters of 2 mm, 3 mm, and 4 mm were artificially generated and nominal and measured hole sizes were compared. Results: Precision of Cart.Vol_ST_RMSCV% was 1.35%. The mean biases between nominal hole volume and measurements were −0.49 ± 1.5 mm 3 (2 mm), −0.41 ± 4.2 mm 3 (3 mm) and +0.34 ± 4.4 mm 3 (4 mm). ST_RMSSD was 100 times lower than the biological variation and the highest bias to measure volume was 24 times lower. Cart.Th results statistically differed among core extraction locations: 1.75 ± 0.28 mm (LAT), 1.84 ± 0.40 mm (MP) and 2.32 ± 0.41 mm (MA). Conclusion: With a standard laboratory micro-CT system, it was possible to measure cartilage volume and thickness with good precision and accuracy relative to the biological variation of the specimen cohort. Cartilage measurements from micro-CT probably will improve the knowledge of the relationship between cartilage and subchondral bone and may allow to better understand the OA process.